Measuring financial inclusion in developing economies: a multidimensional index / Nur Amirah Borhan, Ruhaini Muda and Saadiah Mohamad - Borhan, Nur Amirah; Muda, Ruhaini; Mohamad, Saadiah (Universiti Teknologi MARA, 2021)
Financial inclusion is a major policy concern especially in developing economies. However, an established measure of financial inclusion is still absent. This paper aims to fill this gap by measuring and examining the level of financial inclusion in 66 developing economies. A Financial Inclusion Index (FII) was constructed, incorporating five indicators (ATM, Bank, Other Financial Institutions, Deposits and Loans) for 2013 until 2019. Twostaged Factor Analysis was employed for weights assignment. The results showed that the average level of financial inclusion in developing economies was low but with significant variation among group of countries. A lower level of financial inclusion was observed among the African countries as well as the low-income and lower-middle income countries. The paper also analysed the relationship between financial inclusion and economic development. The findings showed that more developed economies had higher income and thus, higher financial inclusion. While the index is valid and reliable to be used for comparison among developing economies, the study was unable to include indicators of mobile and internet banking due to data constraints. Despite this caveat, the findings of this study will be useful for policymakers in shaping financial inclusion policies.